The 1924 Belagavi Congress Session: Provincial Nationalism and the Making of Democratic Karnataka - Basavarajeshwari R. Patil, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The 1924 Belagavi Congress Session was a landmark of provincial nationalism during the Quit India Movement, highlighting how local activism shaped India’s freedom struggle and post-independence governance. This study explores the session as a convergence of local leadership, women’s participation, grassroots organization, and cultural mobilization, making Belagavi a centre of political consciousness in northern Karnataka. Despite British repression, leaders and volunteers organized rallies, strikes, underground publications, and Swaraj Committees, which acted as proto-democratic village institutions. Women played a vital role in mobilizing communities, leading marches, and managing committees, broadening the movement’s reach. The session also promoted cultural nationalism through folk songs, street plays, and Swadeshi industries. By linking local grievances with national goals, the Belagavi session strengthened the Quit India Movement and laid foundations for democratic governance, influencing Panchayati Raj institutions, cooperative societies, and political culture in Karnataka. It demonstrates how provincial activism transformed India’s freedom struggle into a participatory, democratic process, bridging national vision with local action.
Keywords: Belagavi 1924; Provincial nationalism; Quit India; Grassroots democracy; Swaraj Committees; Women leaders; Karnataka politics